2020
DOI: 10.1038/s41598-020-77626-6
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic response of cerebral blood flow to insulin-induced hypoglycemia

Abstract: The dynamics of cerebral blood flow (CBF) at the onset of hypoglycemia may play a key role in hypoglycemia unawareness; however, there is currently a paucity of techniques that can monitor adult CBF with high temporal resolution. Herein, we investigated the use of diffuse correlation spectroscopy (DCS) to monitor the dynamics of CBF during insulin-induced hypoglycemia in adults. Plasma glucose concentrations, cortisol levels, and changes in CBF were measured before and during hypoglycemia in 8 healthy subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
3
0
1
Order By: Relevance
“…It is also possible that the pericyte energy switch is reserved for pathological conditions such as hypoglycemia, a common occurrence in diabetic individuals, where it might serve as an emergency failsafe that has evolved to protect brain energy supply by increasing blood flow. In support of these ideas, as parenchymal glucose approaches 0, blood flow has been observed to increase by up to 57% (ref 35), and insulin-induced hypoglycemia increases blood flow by 42% in adults 53 .…”
Section: Discussionmentioning
confidence: 90%
“…It is also possible that the pericyte energy switch is reserved for pathological conditions such as hypoglycemia, a common occurrence in diabetic individuals, where it might serve as an emergency failsafe that has evolved to protect brain energy supply by increasing blood flow. In support of these ideas, as parenchymal glucose approaches 0, blood flow has been observed to increase by up to 57% (ref 35), and insulin-induced hypoglycemia increases blood flow by 42% in adults 53 .…”
Section: Discussionmentioning
confidence: 90%
“…Early fMRI studies on healthy humans ( Anderson et al, 2006 ; Driesen et al, 2007 ) and rats ( Kennan et al, 2000 ) found a reduced blood flow response to stimulation during low blood sugar, attributing this phenomenon to impaired NVC. However, during hypoglycemia, the basal CBF increases to ensure glucose supply to brain neurons ( McManus et al, 2020 ; Nippert et al, 2022 ), thought to be related to adenosine-induced increases in astrocyte Ca2+ signaling ( Nippert et al, 2022 ). The mentioned studies did not record neuronal activity, and the observed changes in blood flow responses by fMRI might also be influenced by the increased basal CBF during hypoglycemia ( McManus et al, 2020 ; Nippert et al, 2023 ).…”
Section: Hypoglycemia and Impaired Nvcmentioning
confidence: 99%
“…However, during hypoglycemia, the basal CBF increases to ensure glucose supply to brain neurons ( McManus et al, 2020 ; Nippert et al, 2022 ), thought to be related to adenosine-induced increases in astrocyte Ca2+ signaling ( Nippert et al, 2022 ). The mentioned studies did not record neuronal activity, and the observed changes in blood flow responses by fMRI might also be influenced by the increased basal CBF during hypoglycemia ( McManus et al, 2020 ; Nippert et al, 2023 ). In a recent study, Nippert et al (2023) simultaneously monitored the responses of neurons and blood vessels in the somatosensory cortex of awake healthy mice to whisker stimulation.…”
Section: Hypoglycemia and Impaired Nvcmentioning
confidence: 99%
“…В последнее время появились сообщения, что динамика мозгового кровотока может играть защитную роль при гипогликемии. Мозговой кровоток у здоровых добровольцев после введения инсулина увеличивается на 42%, и это происходит существенно раньше появления симптомов гипогликемии [57]. Надо отметить, что исследования воздействия гипогликемии на мозг человека имеют ограничения, поскольку позволяют оценить лишь связь в основном тяжелых эпизодов с изменениями структуры, реже -функциональных тестов с результатами нейропсихологического обследования.…”
Section: нейрокогнитивные и церебральные измененияunclassified